Monitoring Dan Mentoring Untuk Meningkatkan Kemampuan Kepala Sekolah Dalam Supervisi Akademik Di SMP Negeri 4 Arga Makmur - Ketut Sudarta (Universitas Prof. Dr. Hazairin, S.H, 2017)
Through monitoring and mentoring by supervisors the supervisor can improve the principal's ability to plan, implement, analyze results data, and provide feedback on the follow-up plan for improvement of learning process at SMP Negeri 4 Arga Makmur. Mentors are trusted to guide, assist, support, and encourage others to achieve learning goals, maximize potential, develop skills, improve performance, and achieve established goals. While mentoring not only transfers knowledge and experience, but also transfers emotions and paradigms that are very effective in the development and empowerment of individuals as independent learners in the field.